Paranaense Museum: Paths, Contexts, Museological Actions and Interactions with Society (PhD) (Cadernos de Sociomuseologia, 2020)
This research deals with the museological actions developed in the Museu Paranaense in three distinct periods: from 1874 to 1902 – under management of Agostinho Ermelino de Leão –, from 1902 to 1928 – under management of Alfredo Romário Martins – and from 2011 to 2017 – under management of Renato Augusto Carneiro Junior –, with the purpose of evaluating, in their historical moments, the relations of these actions with the local society at the time, its collections, buildings and documents, besides analyzing the importance of the management in the development of the museum, as well as the societies served, from the relations exercised by its directors. The reasons for the invisibility of Museu Paranaense in brazilian museological context up to the present day were studied, although their different actions have taken place since the 19th century. The data were collected from a participatory methodology, with the involvement of the museum team. The research brought as one of its conclusions the alteration of the date of foundation to 1874, being presented several references for that. The analysis of the information obtained sought to contribute to a re - reading of the historiography of Brazilian museums, including the Museu Paranaense in the 19th century Brazilian museum circuit, as a regional museum that has in its trajectory innovative actions of interaction with local society and that can collaborate in the reflections of the Brazilian and international museological field. This research is finished with the presentation of suggestions of strategies which aim the implementation of improvements in the museological actions developed in the present time, as well as the promotion of the relations of the museum with the society of Paraná and Curitiba, considering its social, cultural, political and economic diversity.Keywords: Brazilian museums. History of museums. Museology. Social function of museums. Sociomuseologia.